PERIODOGRAM AND WAVELET ANALYSIS OF THE SEMI-REGULAR VARIABLE SUPERGIANT Y CVN - Kudashkina, L. S.; Andronov, I. L. (Одеські астрономічні публікації, 2010)
Time series analysis of the bright cold carbon SR-type star Y CVn was studied. The star belongs at a rare subclass "J" and has a separate asymmetric envelope. It is assumed that no "s" process takes place in this star. Due to this, Y CVn may belong not to the AGB, but to the RGB stage, or to a stage of helium burning in a nucleus after a helium flash. The data from the published international databases of AFOEV (France) and VSOLJ (Japan) were studied using the periodogram and wavelet analysis and the unning sine" approximation. The cycle of variations is 267d (varying from 247d to 343d which are superimposed on 1000d -10000d waves.